STRATEGI PROGRAM PADAT KARYA OLEH DINAS SUMBER DAYA AIR DAN BINA MARGA KOTA SURABAYA (STUDI PROYEK PADAT KARYA PAVING TAMBAKSARI SURABAYA) - Sari, Yoan Wandan; Meirinawati, Meirinawati (Publika, 2024)
Padat Karya Surabaya City Program is is a community empowerment program as a government effort to overcome poverty and unemployment in Surabaya. DSDABM Surabaya runs this program through paving production and installation. This program is a program that is widely highlighted by online media because of its success in being able to reap a turnover of 6-7 million rupiah per month for business actors, but this income decreases over time. The absence of production targets from DSDABM is one of the factors in the decline in income because business actors feel free in production and become negligent. This research aims to describe the strategic management of the Padat Karya Program by DSDABM Surabaya using descriptive qualitative research methods. The research focus is based on Rahajeng Widya's strategic management process theory, including formulating strategies, implementing strategies, and evaluating strategies. The location of this research is located at the DSDABM Office and the paving production site in Tambaksari by involving research subjects, namely DSDABM staff and business actors. Data obtained through observation, interviews, and documentation will be analyzed through data collection, data reduction, data presentation, and conclusion drawing. The results showed that DSDABM Surabaya has maximized the Padat Karya Program for paving production through its strengths by providing training, mentoring, financial assistance, facilities and infrastructure assistance, and service facilities to business actors. However, there are obstacles such as the mentality of business actors, the absence of production targets, inadequate tools/machines, lack of socialization, and lack of marketing. Suggestions include: 1) Hold regular socialization, 2) Setting a minimum production target, 3) Collaborating with other agencies and private companies, 4) Promoting sanctions, 5) Maximizing the use of the Padat Karya website.